Yield and nutrient uptake of summer green gram [Vigna radiata (L) Wilczek] under different levels of phosphorus and Sulphur fertilizations - Bairwa, RK; Nepalia, V; Balai, CM; Jalwania, R; Meena, HP (SAARC Journal of Agriculture, 2014)
A field experiment was conducted at Krishi Vigyan Kendra, Dungarpur (Rajasthan) during summer seasons of 2010 and 2011 on sandy clay loam soil to investigate the effect of phosphorus (control, 10, 20, 40 and 60 kg P2O5 ha-1) and sulphur (control, 15, 30 and 45 kg S ha-1) application on NPK and S uptake by green gram [Vigna radiata (L) Wilczek]. Increasing levels of phosphorus up to 60 kg P2O5 ha-1 resulted in significantly higher grain (745 kg ha-1) and stover (1245 kg ha-1) yields and uptake of NPK and S by grain, stover and the whole plant over lower levels of phosphorus during both the years of the study as well as on pooled basis. But it was at par with 40 kg P2O5 ha-1 in respect to S uptake by grain during 2011, S uptake by stover during both the years and total S uptake during 2011. 45 kg S ha-1 produced significantly higher grain (743 kg ha-1) and stover (12264 kg ha-1) yields and uptake of NPK and S by grain, stover as well as total uptake over lower levels of sulphur during both the years of the investigation and on pooled basis. Interaction effect was significant in respect to total NPK and S uptake on pooled basis. Combined application of 60 kg P2O5 ha-1 and 45 kg S ha-1 resulted in significantly higher uptake of total NPK and S by summer green gram DOI: http://dx.doi.org/10.3329/sja.v12i1.21122 SAARC J. Agri., 12(1): 162-172 (2014)